(International Efforts to Combat Climate Change: Turkey as a Case Study) (قضايا سياسية, 2025)
The rapid climate change poses a real threat to the entire world, necessitating international efforts to combat and mitigate it as much as possible. The topic of this research focuses on a clear and serious international model in confronting climate change, which is the Turkish model. Turkey, being a pivotal country with a strategically diverse geographical location, is significantly affected by the rapid climate changes. Therefore, Turkey plays an important role in this field by participating in a range of agreements, programs, and protocols aimed at reducing greenhouse gas emissions through the transition to a green economy, diversifying renewable energy sources, increasing the efficiency of clean energy, and implementing environmentally friendly technologies. Additionally, Turkey is adapting to the effects of climate change by developing infrastructure that aligns with climate changes and preparing disaster response plans. Crucially, Turkey emphasizes financing climate activities by providing financial support to local institutions and ministries concerned with the environment and climate, aiding them in facing climate change challenges. Furthermore, the Turkish government is a member of major international agreements such as the United Nations Framework Convention on Climate Change (UNFCCC), which is the general framework for international cooperation on climate issues, and the Kyoto Protocol, which sets legally binding targets for reducing greenhouse gas emissions for developed countries. Turkey is also a party to the Paris Agreement, which aims to limit global temperature rise to less than 2 degrees Celsius above pre-industrial levels. On the domestic level, Turkey places great importance on the issue of climate change and has taken several steps to address it, including national policies like the National Climate Change Strategy, and investing in renewable energy, with rapid growth observed in the sectors of solar and wind energy. Internationally, Turkey actively participates in international forums on climate change, cooperates with other countries to exchange expertise and technology, and implements various projects to adapt to the effects of climate change, such as water management, coastal protection, and sustainable agriculture.Finally, the research highlights the political conflicts before and after the recent presidential elections and the role of political opposition in hindering the Turkish government's efforts to address climate change both internationally and locally. It examines the economic impacts of the election results, and the influence on environmental laws and regulations, agriculture, tourism, and the economy in general, following the victory of the Justice and Development Party led by Recep Tayyip Erdogan. The possibility of implementing electoral promises through adopting green government policies and developing innovative technological solutions to confront climate change is also considered.